Variety of rumen microbial populations involved in biohydrogenation related to individual milk fat percentage of dairy cows - Zhang, Lei; Shen, Hong; Zhang, Jiyou; Mao, Shengyong (Frontiers in Veterinary Science, 2023)
Our objective was to investigate the contribution of the rumen microbiome on the individual milk fat percentage (MFP) of Holstein dairy cows under the same nutritional and management conditions. From 92 early lactation dairy cows, the top 10 with the highest MFP (HF; n = 10) and the last 10 with the lowest MFP (LF; n = 10) were selected for the study. As a result, the milk trans-10, cis-12 C18:2 content was significant lower in the HF group than that in the LF group (P < 0.001). The rumen acetate to propionate ratio was significant higher in the HF group than that in the LF group (P = 0.035). According to the results of 16S rRNA gene sequencing, a minor but significant difference existed between the groups (P = 0.040). Three genera of the family Lachnospiraceae and four genera of the order Bacteroidales were identified to be the biomarkers for the LF group and HF group in the LEfSe analysis, respectively. Three microbial modules enriched by the family Lachnospiraceae were positively related to the milk trans-10, cis-12 C18:2 content (rs > 0.60, P < 0.05). According to the results of shotgun metagenome sequencing, three kinds of linoleic acid (LA) isomerase genes were present in the gene pools of the rumen microbiome. Among them, the relative abundance of Bifidobacterium LA isomerase (BBI) was higher in the HF group than that in the LF group (P = 0.007). Three metagenome-assembled genomes (MAGs) with LA isomerase genes were positively correlated to the milk trans-10, cis-12 C18:2 content (rs> 0.40, P < 0.05). Furthermore, all of these three MAGs were found to be able to produce lactate. Taken together, these results indicate that the increased relative abundance of microbial population with the trans-10 biohydrogenation pathway within the rumen microbiome contributes to the decrease of MFP via the increase of rumen trans-10, cis-12 C18:2 production. This study provides a new perspective for the development of measures for improving the milking performance of dairy cows.